Household Waste Management in Siddharthanagar Municipality: Practices, Challenges, and Solutions (Rupandehi Campus Journal, 2025)
This study analyzes household waste management practices in Siddhartha nagar Municipality, Rupandehi District, Nepal. Using a mixed-method, cross-sectional design, data were collected from 174 households through questionnaires and analyzed using descriptive statistics and thematic analysis. The findings show challenges such as poor infrastructure, lack of equipment, and limited public awareness. The study emphasizes the need for collaboration between local governments and communities. It recommends awareness programs, improved waste collection systems, and community involvement to promote effective and sustainable waste management and reduce landfill waste in rural municipalities.